Four Medical Ethics Team-Based Learning Modules - Margaret M. Gaffney; Ann Hirschman Cottingham (Association of American Medical Colleges, 2012)
Abstract Introduction Social and behavioral sciences have been integrated into our basic science courses to effectively link basic, behavioral, and clinical science content at a foundational level for medical students. This educational resource provides the information and materials for four medical ethics team-based learning (TBL) modules. These experiences have been used at our institution as an ethics thread running through our first-year medical school physiology course. Methods These modules cover the topics of informed consent, duty to warn, futility, and organ donation. It follows the standard team-based learning format. All sessions are cofacilitated by a physiology faculty and an ethicist. Results All sessions were very well-received by students. Student individual readiness assurance test scores indicated that most students had prepared for class by reading the required materials. Comparison of student individual readiness assurance test and group readiness assurance test scores indicated that team discussion was effective in improving student understanding of the ethical issues. Student response to the group application questions demonstrated sophisticated ethical reasoning. Discussion This resource could be integrated into many case-based health provider courses, with appropriate facilitation expertise. This resource has been integrated into the first-year, second semester physiology course at our school for three reasons: (1) course faculty were interested in integrating ethics content and welcomed ethics cofacilitators, (2) the course was case-based and so easily modified to include ethics case content, and (3) students were able to build on a foundation of ethics already learned in the first semester.